Energy-Efficient Cloud Computing: A Survey - Mohammed Marzook Fathima Fahima; Abul Hassan Sahna Sreen; Sinna Lebbe Fathima Ruksana; Mohamed Hasan Mohamed Majid (Interkoneksi: Journal of Computer Science and Digital Business, 2025)
This comprehensive assessment examines the rising energy usage and environmental risks linked with the rapid growth of cloud computing. It investigates a variety of technologies and tactics targeted at enhancing cloud computing's energy efficiency and sustainability. The research looks at the complexities of cloud computing, examining how diverse applications, workloads, and server designs affect performance and energy consumption. It emphasizes virtualization and consolidation as major strategies for optimizing energy utilization. The notion of "green cloud computing", which combines server virtualization, liquid cooling, and renewable energy sources, is investigated for its ability to minimize carbon emissions and promote sustainability. The review also goes into software-level strategies to improve energy efficiency, such as power-awareness, bio-inspired methodologies, and thermal management. The study underlines the growing importance of energy efficiency in information technology, as well as the role of cloud computing in lowering overall energy usage. It describes numerous energy-saving solutions, particularly those optimized for integrated systems that include both computer systems and networks, with the potential to minimize software and hardware expenses across data centers running cloud applications. Improving load balance is also stressed for improved service quality and performance. However, implementing energy-efficient solutions in cloud computing systems is not without its difficulties. Infrastructure management becomes more complicated, certain strategies may necessitate additional resources, and switching to energy-efficient technologies can be intimidating, particularly for organizations with existing infrastructures. Integrating new energy-saving technologies into existing systems and networks can take time, since rigorous trade-off analysis is required to balance energy efficiency with performance and service quality. In conclusion, this paper provides a thorough overview of the cloud computing energy-efficiency landscape, emphasizing the importance of energy-efficient solutions in mitigating environmental issues and promoting sustainability within the cloud computing sector while acknowledging the complexities and challenges associated with their implementation.